2018
DOI: 10.1159/000486745
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Epithelial <b><i>Stat3</i></b> in Amelogenesis during Mouse Incisor Renewal

Abstract: The aim of this study was to evaluate the role of epithelial signal transducer and activator of transcription 3 (STAT3) in mouse incisor amelogenesis. Since Stat3 is expressed in the epithelial component of developing and adult mouse teeth, we generated and analyzed Krt14Cre/+;Stat3fl/fl mutant mice in which Stat3 was inactivated in epithelia including ameloblast progenitors and ameloblasts, the cells responsible for enamel formation. Histological analysis showed little enamel matrix in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…All previous studies reported a high frequency of persistent primary teeth with delayed primary tooth exfoliation and permanent tooth eruption [11,12,15,16,22]. It was already shown that STAT3 has a role in amelogenesis, pulp stem cell differentiation, and bone development [29]. The lack of late eruption of permanent teeth or the lack of persistence of primary teeth can be attributed to regular dental care, namely the extraction of teeth to prevent further complications.…”
Section: Discussionmentioning
confidence: 99%
“…All previous studies reported a high frequency of persistent primary teeth with delayed primary tooth exfoliation and permanent tooth eruption [11,12,15,16,22]. It was already shown that STAT3 has a role in amelogenesis, pulp stem cell differentiation, and bone development [29]. The lack of late eruption of permanent teeth or the lack of persistence of primary teeth can be attributed to regular dental care, namely the extraction of teeth to prevent further complications.…”
Section: Discussionmentioning
confidence: 99%
“…This implied that the enamel formation from endothelial cells was also influenced by Stat3-deficient dental mesenchyme. Similarly, Bin Zhang et al reported that the loss of Stat3 in dental endothelial cells ( Krt14 - Cre ; Stat3 fl/fl ) caused delayed incisor amelogenesis and dentin abnormalities [ 16 ]. Signals from the dental mesenchyme have been shown to affect HRES in several mouse knockout studies, further supporting our hypothesis [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies reported that loss of Stat3 in mesenchyme exhibited skeletal malformations and mineralization abnormalities in mice [ 13 , 14 ]. As some studies reported, Stat3 is expressed in dental epithelial cells and odontoblasts during tooth development [ 15 , 16 ]. Bin Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation